Prediction of Soil Water Characteristic Curve Based on Soil Water Evaporation - Gaoliang Tao; Da Lei; Lisheng Liu; Yi Li; Xueliang Zhu (Advances in Civil Engineering)
Soil water characteristic curves (SWCC) and soil water evaporation curves both represent the laws of water content variation in the natural state. Aiming to investigate the relationship between them further, Hunan sand with six dry densities were used in this study, and a series of experimental studies were performed. This study developed the application of evaporation curves in geotechnical engineering, reduced the workload of measuring soil water characteristic curves, and explored the relationship between evaporation rate and fractal dimension. Through the indoor tests, we measured soil water characteristic curves of specimens and soil water evaporation curves at different temperatures and explored the relationship between these two curves. In this study, a model was developed that allows the conversion from soil water evaporation curves to soil water characteristic curves, which is an equation about matrix suction ψ versus cumulative time t. Further, two prediction methods are developed, which are derived based on the Fredlund–Xing model and based on the Bird model, respectively. The proposed methods were validated using soil water evaporation tests of Hunan sand with six dry densities at three ambient temperatures, and the results showed that good prediction performances were achieved using these two methods.